PERAN MASJID DAN SEKOLAH MUHAMMADIYAH SEBAGAI PUSAT PENGEMBANGAN PENDIDIKAN ISLAM - Dwi P, Endah (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2022)
This study aims to determine the role of Muhammadiyah mosques and schools as centers of Islamic Education. The Muhammadiyah organization which is one of the major religious organizations in Indonesia has its own role for Islamic education. The method used in this research is a literature study. By obtaining data from books, journals, internet, and other sources related to the role of Muhammadiyah mosques and schools as centers of Islamic Education. Then, the data was analyzed qualitatively which was arranged systematically. With the results of the research that the mosque has an important role as a center of Islamic Education. Because the mosque is the main educational institution. There are many community activities, one of which is Islamic education such as dawn cults and youth studies at night, weekly Islamic education in the form of TPQ, recitations for women in ta'lim assemblies and sermons for the elderly, and activities containing Islamic education on a monthly and annual scale are commemorations Isra' Mi'raj and Maulid Nabi. Besides that, other annual activities are Islamic activities in the month of Ramadan and also the implementation of Ida'in prayers (Eid al-Adha and Eid al-Fitr). In addition, Muhammadiyah schools also have a role as centers of Islamic education. Because there is Arabic or Hijaiyah, worship, aqoid or aqidah, dates, Al-Qur'an, and Muhammadiyah. Another special feature is the existence of moral subjects that teach about aqeedah and aqoid. These subjects contain matters of faith such as the pillars of Islam, the pillars of faith, and others.